Ruteo formal de recolección, transporte y disposición final de los residuos sólidos de la ciudad de Moyobamba - Herrera Sanchez, Cesar Augusto (2016)
This research work is called "DESIGN COLLECTION ROUTES OF MUNICIPAL SOLIO WASTE DISTRICT MOYOBAMBA 2012"; in which, a study was made of the most important characteristics of the locality with respect to the following: current status of the conventional system of collection and transportation of municipal solid waste, study the sense of p~blic roads, mainly streets, tattered and main avenues of urban and periurban part of the city, quantifying length of both streets paved and unpaved, also a study of .pendientes both strong, moderate and became soft. Besides study and projection of urban and peri-urban physical segmentation of the city was made, all with the main objective of which demonstrates formulation of the proposed design collection routes Municipal Solid Waste District of Moyobamba. Through this study it will be achieved strengthen the integrated management of solid waste from the city of Moyobamba, the same one that fits stages of collection and transport 1 Solid Waste comprising much of the system of solid waste management in the city Moyobamba. With this modest, but significant research we are generating the instrument of municipal management, detaíled through the generation of technical documentatíon that demonstrates to decision mal<ers of the current municipal administration.